Refinancing Risk and Debt Maturity Choice during a Financial Crisis - Alemu Tulu Chala (Lund University, School of Economics and Management, Department of Economics, 2018)
This paper explores whether refinancing risk is an important determinant of maturity decisions by investigating how firms with refinancing risk choose the maturity of new loans they obtain during the 2007-2009 financial crisis. The firms' refinancing risk is measured by the maturing portion of outstanding long-term debt. The result shows that firms with a high refinancing risk choose longer maturities. This effect is stronger for speculative-grade and low-cash-flow firms. There is also evidence that firms with refinancing risk obtain longer maturities from their relationship lenders.
Keywords: G01; G32; G39; 330; Refinancing risk; Debt maturity; financial crisis